Climatic windows for human migration out of Africa in the past 300,000 years - Robert M. Beyer; Mario Krapp; Anders Eriksson; Andrea Manica (Nature Communications, 2021)
It is still unclear when and by which route modern humans expanded out of Africa. Here, Beyer et al. use paleoclimate reconstructions and estimates of human precipitation requirements to evaluate the survivability of spatial and temporal migration corridors to Eurasia over the last 300,000 years.